α-amylase Inhibitor Based on Oleanolic Acid: In vitro and in silico Studies - Huyen, Pham Ngoc; Trang, Nguyen Thi Quynh; Anh, Nguyen Thi Van; Chu, Luan Luong (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5831, 2025)
Alpha-amylase (α-amylase) is a critical enzyme in carbohydrate metabolism, catalyzing the hydrolysis of α-1,4-glycosidic bonds in starch. Inhibition of α-amylase activity is an effective strategy for managing metabolic disorders like diabetes and obesity by reducing postprandial glucose levels. This study evaluated the α-amylase inhibitory potential of oleanolic acid (OA), a pentacyclic triterpenoid extracted from Panax bipinnatifidus Seem., using a combined in vitro and in silico approach. In vitro , the assays demonstrated that OA inhibited α-amylase with an IC 50 value of 198.73 μg/mL, which, while less potent than the standard inhibitor acarbose (IC 50 ~ 22.48 μg/mL), showed promise as a natural compound with inhibitory activity. In silico molecular docking studies provided insights into the interaction mechanisms between OA and α-amylase. OA displayed a strong binding affinity with a binding energy of -8.33 kcal/mol, significantly lower than acarbose (-2.90 kcal/mol). Key residues, including TYR62, ASP197, GLU233, HIS101, and LEU162, were identified as contributors to hydrogen bonding and hydrophobic interactions with OA. Although acarbose formed more hydrogen bonds with residues such as GLU233, ASP300, and GLY304, OA exhibited stable binding characteristics and a distinct interaction profile. These findings suggest that while OA has lower in vitro potency compared to acarbose, its strong binding affinity and interaction with critical active site residues make it a promising candidate for further optimization and development as a natural α-amylase inhibitor. The study highlights the potential of OA for therapeutic applications in metabolic disorder management, emphasizing the need for structural modifications or combination strategies to enhance its efficacy.